Up-Front Multigene Panel Testing for Cancer Susceptibility in Patients With Newly Diagnosed Endometrial Cancer: A Multicenter Prospective Study. (2021) - Levine, Monica D.; Pearlman, Rachel; Hampel, Heather; Cosgrove, Casey; Cohn, David; Chassen, Alexis; Suarez, Adrian; Barrington, David A.; McElroy, Joseph P.; Waggoner, Steven; Nakayama, John; Billingsley, Caroline; et al.
Abstract : PURPOSE: Clinical utility of up-front multigene panel testing (MGPT) is directly related to the frequency of pathogenic variants (PVs) in the population screened and how genetic findings can be used to guide treatment decision making and cancer prevention efforts. The benefit of MGPT for many common malignancies remains to be determined. In this study, we evaluated up-front MGPT in unselected patients with endometrial cancer (EC) to determine the frequency of PVs in cancer susceptibility genes. METHODS: Patients with EC were prospectively enrolled at nine Ohio institutions from October 1, 2017, to December 31, 2020. Nine hundred and sixty-one patients with newly diagnosed EC underwent clinical germline MGPT for 47 cancer susceptibility genes. In addition to estimating the prevalence of germline PVs, the number of individuals identified with Lynch syndrome (LS) was compared between MGPT and tumor-based screening. RESULTS: Likely pathogenic variants or PVs were identified in 97 of 961 women (10.1%). LS was diagnosed in 29 of 961 patients (3%; 95% CI, 2.1 to 4.3), with PVs in PMS2 most frequent. MGPT revealed nine patients with LS in addition to the 20 identified through routine tumor-based screening. BRCA1 and BRCA2 PVs were found in 1% (10 of 961; 95% CI, 0.6 to 1.9) of patients and that group was significantly enriched for type II ECs. CONCLUSION: This prospective, multicenter study revealed potentially actionable germline variants in 10% of unselected women with newly diagnosed EC, supporting the use of up-front MGPT for all EC patients. The discovery that BRCA1 or BRCA2 heterozygotes frequently had type II cancers points to therapeutic opportunities for women with aggressive histologic EC subtypes.